Inferring physiological energetics of loggerhead turtle (Caretta caretta) from existing data using a general metabolic theory. (May 2017) - Marn, Nina; Kooijman, S.A.L.M.; Jusup, Marko; Legović, Tarzan; Klanjšček, Tin
Abstract: Loggerhead turtle is an endangered sea turtle species with a migratory lifestyle and worldwide distribution, experiencing markedly different habitats throughout its lifetime. Environmental conditions, especially food availability and temperature, constrain the acquisition and the use of available energy, thus affecting physiological processes such as growth, maturation, and reproduction. These physiological processes at the population level determine survival, fecundity, and ultimately the population growth rate—a key indicator of the success of conservation efforts. As a first step towards the comprehensive understanding of how environment shapes the physiology and the life cycle of a loggerhead turtle, we constructed a full life cycle model based on the principles of energy acquisition and utilization embedded in the Dynamic Energy Budget (DEB) theory. We adapted the standard DEB model using data from published and unpublished sources to obtain parameter estimates and model predictions that could be compared with data. The outcome was a successful mathematical description of ontogeny and life history traits of the loggerhead turtle. Some deviations between the model and the data existed (such as an earlier age at sexual maturity and faster growth of the post-hatchlings), yet probable causes for these deviations were found informative and discussed in great detail. Physiological traits such as the capacity to withstand starvation, trade-offs between reproduction and growth, and changes in the energy budget throughout the ontogeny were inferred from the model. The results offer new insights into physiology and ecology of loggerhead turtle with the potential to lead to novel approaches in conservation of this endangered species. Graphical abstract: Highlights: Full life cycle DEB model for loggerhead turtle energetic presented. Parameters estimated using assimilation of disjointed datasets into the model. Life history traits follow from parameter values and environmental conditions. Time to reserve depletion suggests mid-sized turtles are able to starve for a year. Investment into reproduction is suboptimal, allowing a larger maximum body size.